PENERAPAN MEDIA PANCING ATURAN (PAPAN) PADA MATERI ATURAN DI LINGKUNGAN SEKITAR DALAM MENUMBUHKAN MOTIVASI BELAJAR KELAS IV SEKOLAH DASAR - Khakimah, Frika Fatekhatul; Ismiyanti, Yulina; Sari, Yunita (Universitas Negeri Medan, 2025)
Education plays a very important role in life; nothing can be separated from education. Education is a planned process that aims to develop knowledge, skills, attitudes, and moral values. The aim of this research is to explain the application of regulatory fishing media (PAPAN) to regulatory material in the surrounding environment in fostering learning motivation for class IV at SD Sultan Agung 4 Semarang. The type of research uses case studies with a qualitative approach whose collection techniques use observation, interviews, and documentation. The data obtained was analyzed using three techniques, namely data condensation, data presentation, and drawing conclusions. Then it was checked using triangulation techniques in the form of triangulation of sources, techniques, and time. The results of the research show that Media Fishing Rules (PAPAN) has proven to be effective in increasing the learning motivation of class IV students at SD Sultan Agung 4 Semarang. This media helps students understand the rules of everyday life in an interesting and contextual way and encourages active involvement, self-confidence, and participation in discussions. However, its effectiveness depends on resource support and teacher skills in managing the classroom. Obstacles such as limited tools and lack of teacher experience need to be overcome through continuous evaluation and improvement. With careful planning, PAPAN can create learning that is interactive, relevant, and has a positive impact on students.